2016
DOI: 10.1515/jim-2016-0025
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Homocysteine Level in the Critically Ill Patient. A Review

Abstract: Increased levels of homocysteine (HCYS) represent a risk factor for a series of physiopathological conditions: mental retardation, cardiovascular and neurodegenerative diseases, Parkinson's and Alzheimer's disease, depression, osteoporosis, endothelial dysfunction and inhibition of cell proliferation. This paper aims to present the pathophysiological implications of HCYS and the correlation of hyperhomocysteinemia (H-HCYS) with critical condition in the intensive care unit (ICU). Hypovitaminosis B and folate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 56 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…One of the main pathologies developed at cardiovascular level is represented by atherosclerosis, which eventually can be defined as a molecular and cellular inflammation complex. [10][11][12][13] Of course, if we were to look at a molecular and cellular level, the vascular endothelium is the main involved cofactor. From a molecular viewpoint, the key player is represented by nuclear transcription factor kappa B (NF-κB), which, according to recent studies, is responsible for the modulation of molecular and epigenetic signals at this level.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main pathologies developed at cardiovascular level is represented by atherosclerosis, which eventually can be defined as a molecular and cellular inflammation complex. [10][11][12][13] Of course, if we were to look at a molecular and cellular level, the vascular endothelium is the main involved cofactor. From a molecular viewpoint, the key player is represented by nuclear transcription factor kappa B (NF-κB), which, according to recent studies, is responsible for the modulation of molecular and epigenetic signals at this level.…”
Section: Introductionmentioning
confidence: 99%
“…The review includes the presentation of new studies that demonstrated an increase of this biomarker in patients with atherosclerosis or with cardiovascular diseases via complex pathways that involve endothelial dysfunction, LDL oxidation and monocyte aggregation. 9 This, together with the observation described in this work, that the level of HCYS is proportional to the incidence of coronary artery disease, raises the question if this biomarker, useful for critically ill patients, could also be used for assessing the cardiovascular status. As for the relation between HCYS and critically ill patients, seven recent studies are presented that prove the relationship between HCYS levels and the deterioration of the clinical condition in these patients.…”
mentioning
confidence: 82%
“…In the review published by Bedreag et al in this issue of JIM, the role of homocysteine levels in predicting the evolution of critically ill patients is presented in a complex manner, from pathophysiological mechanisms involved in its action, to interrelation with different other diseases such as cardiovascular or bone diseases. 9 The relationships between homocysteine levels and particular features of the critically ill patients are described together with the potential of control of homocysteine levels in this category. The review includes the presentation of new studies that demonstrated an increase of this biomarker in patients with atherosclerosis or with cardiovascular diseases via complex pathways that involve endothelial dysfunction, LDL oxidation and monocyte aggregation.…”
mentioning
confidence: 99%
See 1 more Smart Citation